Comparison of Bioreactance and Echocardiographic Noninvasive Cardiac Output Monitoring and Myocardial Function Assessment in Primagravida Women. Issue 3 (September 2017) - Doherty, A.; El-Khuffash, A.; Monteith, C.; McSweeney, L.; Breatnach, C.; Kent, E.; Tully, E.; Malone, F.; Thornton, P.
Abstract : ( Br J Anaesth. 2017;118(4):527–532) Bioreactance (BRT) uses the phase shift or time delay of an applied alternating current traversing the thoracic area to derive stroke volume (SV). Its use has not yet been validated for detailed noninvasive assessment of maternal hemodynamics in the obstetric population. Therefore, the authors of the present study compared simultaneous cardiac output (CO) and SV measurements obtained using a noninvasive CO monitor—NICOM (Cheetah Medical, Newton, MA)—that utilizes BRT and echocardiography in a group of healthy primigravid women. The authors also assessed the relationship between maternal characteristics, such as body mass index, and myocardial performance.